Discovery and photosynthesis of sinuaustones A and B, diterpenoids with a novel carbon scaffold isolated from soft coral Sinularia australiensis from Hainan. Issue 21 (22nd September 2022) - Wu, Meng-Jun; Yu, Dan-Dan; Su, Ming-Zhi; Wang, Jian-Rong; Gong, Lei; Zhang, Zai-Yong; Wang, Hong; Guo, Yue-Wei
Abstract : Two novel diterpenoids, sinuaustones A (1 ) and B (2 ), featuring an unprecedented tricyclo[9.3.1.0 3, 15 ]tetradecane carbon framework were isolated from the South China Sea soft coral Sinularia australiensis . Abstract : Two novel diterpenoids, sinuaustones A (1 ) and B (2 ), featuring an unprecedented tricyclo[9.3.1.0 3, 15 ]tetradecane carbon framework, along with a new spatane-type diterpenoid 3 and two related known compounds 4 and 5, were isolated from the South China Sea soft coral Sinularia australiensis . The structures of the new compounds were established by detailed spectroscopic, X-ray diffraction analysis and quantum chemical computation methods. Photosynthesis of 1 and 2 starting from co-isolated 5 was completed giving insight into the plausible biosynthetic pathway of 1 and 2, as well as their structural relationship with co-occurring 3–5 . In the in vitro bioassay, compounds 1, 2, 3, and 5 exhibited inhibitory effects on lipopolysaccharide (LPS)-induced inflammatory responses in RAW264.7 cells with IC50 values of 20.9, 75.1, 9.1, and 30.4 μM, respectively.